2001
DOI: 10.1116/1.1379316
|View full text |Cite
|
Sign up to set email alerts
|

Physical and electrical properties of noncrystalline Al2O3 prepared by remote plasma enhanced chemical vapor deposition

Abstract: dielectric films have been synthesized by remote plasma enhanced chemical vapor deposition ͑RPECVD͒ and deposited on ͑i͒ H-terminated Si͑100͒ and ͑ii͒ on SiO 2 prepared by remote plasma assisted oxidation and RPECVD on Si͑100͒ substrates using organometallic source gases injected downstream from a He/O 2 plasma. Chemical composition and morphology of the Al 2 O 3 films and their interfaces have been studied by Auger electron spectroscopy ͑AES͒, Fourier transform infrared spectroscopy, nuclear resonance profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
116
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 13 publications
13
116
1
Order By: Relevance
“…46 It has also been hypothesized that H may be involved in the generation of the positive charges. 20 [48][49][50] The negative charges will shift away from the Si interface when using SiO 2 interlayers between Si and Al 2 O 3 . In addition, positive charges associated with SiO 2 need to be taken into account.…”
Section: Capacitance-voltage Measurementsmentioning
confidence: 99%
“…46 It has also been hypothesized that H may be involved in the generation of the positive charges. 20 [48][49][50] The negative charges will shift away from the Si interface when using SiO 2 interlayers between Si and Al 2 O 3 . In addition, positive charges associated with SiO 2 need to be taken into account.…”
Section: Capacitance-voltage Measurementsmentioning
confidence: 99%
“…This negative built-in charge for Al 2 O 3 was also reported by Hezel and Jaeger 6 and Agostinelli et al 7 The negative charge in Al 2 O 3 is suggested to be present at the unique tetrahedrally coordinated Al site present at the interface that has a net negative charge, in contrast to the octahedrally coordination site where Al has a charge of 3+. 17 For the commonly used thermal oxide and a-SiN:H positive built-in charges in the range of 10 10 -10 12 cm −2 are reported, 6,18 and for a-SiC : H the sign of the built-in charge is reported to depend on the wafer doping type. 4,5 A negative built-in charge is especially beneficial for passivation of highly doped p-type silicon.…”
mentioning
confidence: 95%
“…In contrast to the chemical passivation, the field-effect passivation was found to be different as evident from the measured [29][30][31] Consequently it was decided to investigate the surface passivation mechanisms of the Al 2 O 3 stacks reported in this work by corona charging experiments in order to distinguish between the role of chemical and field-effect passivation. Corona charging could not be employed successfully to the samples coated with a-SiN x :H films due to the too low electrical resistivity of the a-SiN x :H films which preclude the surface charging of these films by corona charges.…”
Section: Resultsmentioning
confidence: 99%
“…14,19,50,51 From recent studies it is known that an interfacial SiO 2 layer between the passivation material and the Si has a significant effect on the surface passivation of Al 2 O 3 and a-SiN x :H films as shown for thin ALD, PECVD and thermally grown SiO 2 interlayers. 25,[29][30][31]33 More specifically, from the studies of Dingemans et al it has been clearly observed that the level of field-effect passivation caused by fixed charges in the passivation material depends heavily on the SiO 2 interlayer thickness while the level of chemical passivation remains high. 25,32 This is of interest for solar cells as it might provide identical passivation schemes for n + -and p + -type Si surfaces (so-called symmetrical passivation) which are relevant when passivating both emitter and surface field surfaces at once (e.g., for passivating both sides of conventional cells or the back side of interdigitated back contact cells).…”
mentioning
confidence: 99%